Strategi Digital Marketing Aplikasi Tiktok dalam Meningkatkan Omzet Penjualan Sepeda Motor (Studi Akun Tiktok @6jayamotormalang) - Maulana, Muhammad Naufal Aulia; Widarko, Agus; Saraswati, Ety (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This research aims to find out and analyze the digital marketing strategy of the Tiktok application in increasing motorbike sales turnover carried out by 6 Jaya Motor Malang. This research uses descriptive qualitative methods. The informants in this research consisted of 11 informants who had been determined using purposive sampling techniques. Data collection methods in this research consist of observation, interviews and documentation. This research data analysis uses Miles and Huberman interactive data analysis techniques, Nvivo software, and SWOT analysis. The results of this research show that the digital marketing strategy for the Tiktok Application carried out by 6 Jaya Motor Malang succeeded in achieving an increase in sales turnover as expected. These results show that the right digital marketing strategy can encourage the development of a company, through content creation, implementation of promotions, and services provided to consumers. Keywords: Digital Marketing Strategy, Tiktok Application, Increasing Sales Turnover